Broad-band difference interferometer as a temperature sensor - Gut, Kazimierz; Opilski, Zbigniew (Photonics Letters of Poland, 2014)
The paper presents the characteristics of a broad-band difference interferometer (spectropolarimetric). When a waveguide layer introduces light from a spectral range, at the output structure there is a spectral distribution which depends on the parameters of the propagation wavelength. It shows the effect of temperature on the parameters describing the system. Full Text: PDF References P. Kozma et al. "Integrated planar optical waveguide interferometer biosensors: A comparative review", Biosens. Bioelectron. 58, 287 (2014). CrossRef K. Gut, "A suggestion of utilizing bimodal layers of the polymer SU8 for the purpose of monitoring the changes in the refractive index", Opt. Appl. 42, 407 (2012). CrossRef K. Misakos et al. "Broad-band Mach-Zehnder interferometers as high performance refractive index sensors: Theory and monolithic implementation", Opt. Expr. 22, 8856 (2014). CrossRef M. Kitasara et al. "Integrated optical frequency-resolved Mach-Zehnder interferometers for label-free affinity sensing", Opt. Expr. 18, 8193 (2010). CrossRef M. La Notte, V. Passaro, "Ultra high sensitivity chemical photonic sensing by Mach?Zehnder interferometer enhanced Vernier-effect", Sensor Actuat. B-Chem. 176, 994 (2013). CrossRef K. Gut, "Spectropolarimetric analysis of differential interferometer", Proc. SPIE 9291, 92910N (2014). CrossRef M. Daimon, A. Masumura, "Measurement of the refractive index of distilled water from the near-infrared region to the ultraviolet region", Appl. Optics 46, 3811 (2007). CrossRef K. Gut, S. Drewniak, "Comparison of the Sensitivity of a Polymer Waveguide in the Classical and Reverse Symmetry System", Acta Physica Pol. A. 118, 1133 (2010). CrossRef K. Tiefenthaler, W. Lukosz, "Sensitivity of grating couplers as integrated-optical chemical sensors", J. Opt. Soc. Am. B 6, 209 (1989). CrossRef K. Gut, S. Drewniak, "The Waveguide Structure Based on the Polymer SU8 on a SiO2/Si Substrate", Acta Physica Pol. A 120, 630 (2011). CrossRef C. Delezoide et al. "General approach for the sensitivity analysis and optimization of integrated optical evanescent-wave sensors", J. Opt. Soc. Am. B 31, 851 (2014). CrossRef